The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s12272-010-0706-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of itraconazole-cyclodextrin inclusion complex and its commercial product

Abstract: Itraconazole (ITZ) solid complex using hydroxypropyl-beta-cyclodextrin (ITZ-HP-beta-CD) with 20% polyvinylpyrrolidone was prepared by a co-evaporation method. The complex improved antifungal activity against C. parapasilosis and C. albicans. The complex demonstrated good flow and compressibility characteristics. The complex was formulated as a capsule dosage form and drug release was evaluated. Capsules containing ITZ-HP-beta-CD at a molar ratio of 1:3 with 20% polyvinylpyrrolidone have a faster dissolution ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Various techniques have been used to improve the solubility of poorly water-soluble drugs, including using surfactants, 5 inclusion complexation, 6 , 7 and solid dispersion (SD) techniques. 8 For example, the SD technique has been well used to enhance the dissolution rate of ITZ, 4 , 8 10 and one of the commercial products of ITZ (Sporanox ® ) is a hard capsule form containing ITZ coated on sugar spheres.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been used to improve the solubility of poorly water-soluble drugs, including using surfactants, 5 inclusion complexation, 6 , 7 and solid dispersion (SD) techniques. 8 For example, the SD technique has been well used to enhance the dissolution rate of ITZ, 4 , 8 10 and one of the commercial products of ITZ (Sporanox ® ) is a hard capsule form containing ITZ coated on sugar spheres.…”
Section: Introductionmentioning
confidence: 99%
“…The same results were detected in IBU 3 physical mixture and IBU 3 free drug compared to IBU 45 physical mixture and IBU 45 free drug. Furthermore, the two PMs showed faster dissolution rate than corresponding free drug of IBU3 and IBU 45, which was attributed to the wettability of β-CD and partly forming inclusion complex [32] ( fig. 8, Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…0.0453 mg/ml 4 however, few studies on the water solubility enhancement of TPZ have been reported in the literature. To improve solubility of water insoluble drugs, micelles, 5 inclusion complexation, 6,7 self‐microemulsifying drug delivery systems, and solid dispersion (SD) techniques have been applied in the pharmaceutical industry 8 . Among these technologies, SD has been considered a potential technology to improve the bioavailability (BA) of low‐water soluble drugs by enhancing water solubility and dissolution rate 9 .…”
Section: Introductionmentioning
confidence: 99%